Does a gating policy for ANCA overlook patients with ANCA associated vasculitis? An audit of 263 patients. - Arnold, D; Timms, A; Luqmani, R; Misbah, SA (2010)
BACKGROUND: Antineutrophil cytoplasm antibodies (ANCA) are used as diagnostic markers for small-vessel vasculitis of the Wegener Granulomatosis-microscopic polyangiitis (WG-MPA) spectrum, but if testing is applied indiscriminately, its value is diminished. The authors measured the effect of a targeted ANCA testing policy introduced in our institution in an attempt to improve the diagnostic value of testing in patients with suspected vasculitis. METHODS: The authors measured the rate of ANCA requests at a single regional centre in the year prior to and following the introduction of clinical guidelines to ensure appropriate test usage. The authors also audited clinical outcomes in patients in whom ANCA testing was declined. RESULT: Following implementation of the antineutrophil cytoplasm antibodies (ANCA) gating policy, the number of monthly ANCA tests carried out fell from 287+/-30 to 143+/-18 (p<0.0001) and was associated with an increased rate of positivity, from 18.5% (95% CI 17.0 to 20.1%) to 30.3% (27.5 to 33.1%; p<0.0001). The authors undertook a careful review of the case records from 263 patients in whom testing was declined according to the gating policy over an 8-month period. After 6 months' follow-up, no diagnoses of small-vessel vasculitis of the WG-MPA spectrum were reached. CONCLUSIONS: The rational use of ANCA testing to aid in the diagnosis of vasculitis should include a clinical gating policy to improve diagnostic performance. Adherence to a gating policy for ANCA testing coupled with close liaison between clinician and laboratory does not result in either a missed or delayed diagnosis of small-vessel vasculitis belonging to the WG-MPA spectrum.